The genome sequence of a snakefly, Xanthostigma xanthostigma (Schummel, 1832) [version 1; peer review: 2 approved] - Maxwell V. L. Barclay; Steven Falk; Liam M. Crowley; Emma Taluy (Wellcome Open Research)
We present a genome assembly from an individual male snakefly, Xanthostigma xanthostigma (Arthropoda; Insecta; Raphidioptera; Raphidiidae). The genome sequence has a total length of 623.30 megabases. Most of the assembly (99.74%) is scaffolded into 13 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 17.75 kilobases in length. Gene annotation of this assembly on Ensembl identified 13,251 protein-coding genes.